QUALITY OF MUSIC PEDAGOGICAL EDUCATION (American Journal of Interdisciplinary Research and Development, 2023)
In our country, the process of improving the quality of music pedagogic education and training of professional personnel is underway. In this respect, the quality of music pedagogic education is an integral part of this process, and quality training of music pedagogic personnel through it is relevant. In the new Development Strategy of Uzbekistan, the task of bringing music pedagogic education to the quality stage and quality training of music pedagogic personnel based on the requirements of technological development is set. Therefore, in music pedagogical education, first of all, achieving the quality of education is one of the primary issues.